A relative measurement and monitoring of OTTV of glass facade passive building in tropical climate - Vighio, Anees Ahmed; Zakaria, Rozana; Glinska-Lewczuk, Katarzyna; Munikanan, Vikneswaran; Wahi, Noraziah; Aminuddin, Eeydzah; Ahmad, Faridahanim; Saha, Kamaliah Mohd; Wen, Thong Jin; Pawlowicz, Joanna A. (Journal of Civil Engineering and Management, 2025)
Efficient and productive buildings are vital to sustainable cities, significantly contributing to Sustainable Development Goals (SDGs) 3, 7, 11, and 12. Urban areas are responsible for 80% of global energy consumption, with buildings accounting for 40%. Achieving a healthy and comfortable indoor thermal envelope depends on various factors including building function, location, layout design, openings, and materials. The building facade, particularly glass facades, is a significant contributor to both energy performance and occupant comfort. Despite their importance, few studies focus on real-time measurement and monitoring of the Overall Thermal Transfer Value (OTTV) of passive buildings, especially with glass facades. Glass allows natural light and heat exchange, impacting the overall energy performance and quality of indoor environments. This study investigates the real-time impact of temperature variations on the OTTV of glass facade passive buildings from 8 am to 5 pm, focusing on Malaysia’s tropical climate. The study’s findings revealed that the OTTV varies from 42.642 W/m2 at 11:30 am to 80.341 W/m2 at 10:30 am. The study contributes to the body of knowledge by providing valuable insights regarding the dynamic thermal behaviour of the passive building envelope. Specifically, it demonstrates how OTTV varies with changing climatic conditions such as temperature fluctuations and solar radiation.